Propuesta de una red de espacios verdes públicos para el bienestar de los habitantes del casco urbano de San Pablo del Lago - Ulcuango Yacelga, Erik Paul (2023)
The final project consists of a proposal for a network of public spaces in the urban area and a preliminary project for a Sports Center in the Parish of San Pablo del Lago. The project is deve-loped within the Parish, “The Parish dates back to the 1570s, in which, according to the priest Antonio Borja, it was founded as a town through Ecclesiastical Reduction ordered by Bishop Alonso de la Peña, on June 29, 1576”, (2019-2023 Administration, 2019). According to the analysis carried out in the urban area of San Pablo del Lago, belonging to the Otavalo canton, we can determine that the intervention in this sector is very important and necessary to improve the quality of life of the citizens who live in this place. Therefore, it is proposed that public green spaces are those that predominate in the vegetation and landscape, whose function is to serve for the recreation of the inhabitants and contribute to the environment, also adding that there must be 9 m2 per inhabitant as proposed by the WHO. Therefore, in the analysis carried out, only those green spaces that meet the urban quality condi-tions are taken into account. The work is developed in five chapters: Introduction of the subject, state of the art, Methodology and investigation concluding with the proposal of the architectural draft, which are detailed in the present titling work.